Research handbook on intellectual property and employment law - Bruun, Niklas; Mansala, Marja-Leena; Edward Elgar Publishing (Northampton : Edward Elgar Publishing, 2021)
"This comprehensive Research Handbook explores the rights of employers and employees with regard to intellectual property (IP) created within the framework of the employment relationship. Investigating the development of employee IP from a comparative perspective, it contextualises issues in the light of theoretical approaches in both IP law and labour law. Leading academic experts examine the most crucial building blocks of the regulation of employee IP, such as authorship, inventorship and creatorship, as well as individual, corporate and collective works. Chapters focus on US and European law, but also offer insights from Chinese, Japanese and Korean law. The Research Handbook also tackles new and developing global challenges in the field, including labour mobility, trade secrets, non-compete clauses, university employees, cross-border business matters, and choice of law issues. Scholars and students in both IP and labour law, and particularly those working at the intersection of these fields, will find this Research Handbook invaluable. It will also provide important insights for legislators, business practitioners and university management"--
Contents: Preface / PART I FOUNDATIONS OF EMPLOYEE INTELLECTUAL PROPERTY - HISTORICAL AND METHODOLOGICAL PERSPECTIVES -- 1 foundations of labour and ip law / Niklas Bruun and Marja-Leena Mansala -- 2. The role of the employee-inventor and the institutional development of technology-based business / Ulf Petrusson -- 3. Knowledge economy, changing employment relations, and intellectual property issues / Alan Hyde -- Part II: Regulatory intellectual property framework -- 4. Regulatory development in different fields of ip / Marja-Leena Mansala and Niklas Bruun -- 5. Concepts of authorship and their relevance to ip entitlement - personalist vs entrepreneurial approaches / Antoon Quaedvlieg -- 6. The curious contrast between corporate authorship and inventorship in the United States / Sean M. O'Connor -- 7. Collective works in French law / Sylvie Nérisson and Stéphanie Le Cam -- 8. Fairness for all - employee inventions between contract and legislation in korea and Japan / Nari Lee -- 9. The interface between employment law and enforcement, remedies and sanctions / Trevor Cook -- 10. Comparative perspectives on employee inventions: Chinese developments compared with European, asian and us models / Liguo Zhang -- Part III: Globalization and new challenges -- 11. Cross-border business matters and choice of law / Paul Torremans -- 12. Academic employees in universities: Who can exploit their intellectual property? / Ann L. Monotti -- 13. Knowledge mobility, trade secrets and non-competes: Lessons from the common law tradition / William van Caenegem -- Index.
Includes bibliographical references and index.
Keywords: Intellectual property (International law); Inventions, Employees'.; Copyright, Employees'.; Intellectual capital; dúševné vlastníctvo; pracovné práva; intelektuálny kapitál; elektronické dokumenty